Training methods to increase throwing velocity in baseball athletes: a brief review - Job, T.; Neville, J.; Cahill, M. J.; Bourgeois, F. A.; Crotin, R. L.; Cronin, J. B. (Strength and Conditioning Journal, 2022)
Throwing velocity is a crucial component to success in baseball athletes, especially at the position of pitcher. Through practice and proper instruction, pitchers can refine their pitching mechanics to maximize efficiency and throwing velocity in tandem with improving injury resistance. Non-specific training such as gym-based resistance training has been used concurrently with baseball skills training to enhance athletic abilities, including throwing velocity. Increases in throwing velocity have been observed while training with lighter (greater than 12 repetition maximum [RM]) and heavier (3-12 RM) loads. Specific training such as variably weighted baseballs has also been utilized to facilitate increases in throwing velocity. Throwing velocity has also been successfully increased using balls overweight and underweight than the standard five-ounce baseball. More clarity is needed regarding necessary strength levels, range of motion, and progressions in ball mass or throwing volume when applying this training mode. Training methods to increase throwing velocity in baseball athletes should include resistance training with a variety of loads and throwing variably weighted baseballs within the athlete's capability.